H 2 S-mediated protein persulfidation regulates redox metabolic flux underlying salt-stress resilience in rice - Zhengyao Lin; Mingjian Zhou; Xiaoyun Ma; Miaomiao Li; Ling Fu; Hongfei Li; Yinggao Liu; Fu-Yuan Zhu; Marc Van Montagu; Frank Van Breusegem; Jingjing Huang; Yanjie Xie (Proceedings of the National Academy of Sciences, 2026)
Hydrogen sulfide (H 2 S) functions as a gaseous signaling molecule in plant stress responses through the persulfidation of protein cysteine (Cys) residues. A comprehensive, Cys site-specific map of the plant persulfidome has been lacking, despite its importance for achieving a systems-level understanding of the biological roles of Cys persulfidation. Using a state-of-the-art N -ethylmaleimide-biotin-based proteomics strategy, we generate a dynamic map of 1,691 persulfidated Cys sites in the rice ( Oryza sativa ) leaf proteome. Our results reveal a global dynamic changes in protein persulfidation during prolonged salt stress, with notable impacts on proteins involved in metal-dependent catalysis, redox metabolism, and the pentose phosphate pathway (PPP). Based on these patterns, we investigated the functional relevance of persulfidation within the nonoxidative PPP. H 2 S-mediated persulfidation decreased the activity of the representative nonoxidative PPP enzyme ribose-5-phosphate isomerase, leading to increased NADPH production and subsequent activation of NADPH-dependent redox enzymes, including monodehydroascorbate reductase (MDHAR) isoforms of the ascorbate-glutathione (AsA-GSH) cycle. Persulfidation protected MDHAR3/5 from oxidative inhibition and degradation, thereby sustaining AsA-GSH cycle capacity and supporting reactive oxygen species scavenging. This site-specific persulfidome provides a valuable resource for exploring plant redox regulation, and our functional analyses offer mechanistic insight into how H 2 S-dependent protein persulfidation modulates redox metabolic fluxes to bolster NADPH availability and maintain redox homeostasis during salt-stress adaptation.